Integration of financial markets and national price levels: the role of exchange rate volatility - Mathias Hoffmann; Peter Tillmann (Deutsche Bundesbank, 2008)
How does international financial integration affect national price levels? To analyze this question, this paper formulates a two-country open economy sticky-price model under either segmented or complete asset markets. It is shown that the effect of financial integration, i.e. moving from segmented to complete asset markets, is regime-dependent. Under managed exchange rates, financial integration raises the national price level. Under floating exchange rates, however, financial integration lowers national price levels. Thus, the paper proposes a novel argument to rationalize systematic deviations from PPP. Panel evidence for 54 countries supports the main findings. A 10% larger ratio of foreign assets and liabilities to GDP, our measure of international financial integration, increases the national price level by 0.27 percentage points under fixed and intermediate exchange rate regimes and lowers the price level by 0.3 percentage points under floating exchange rates.
Keywords: F21; F36; F41; 330; International financial integration; exchange rate regime; national price level; PPP; foreign asset position; Internationaler Finanzmarkt; Marktintegration; Preisniveau; Wechselkurssystem; Kaufkraftparität; Auslandsvermögen; Theorie; Welt